Saint Vincent and the Grenadines. Significant achievements 2018 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2019)
The main activities carried out by the Institute in Saint Vincent and the Grenadines during 2018 are identified, with respect to the needs and interests of the country, strengthening issues such as conservación de suelos, gestión de agua, gobernanza y resiliencia contra el cambio climático. Likewise, work was done to improve alliances, as well as support for the Network of rural women producers and the introduction of two new varieties of coffee from Costa Rica, in order to promote the coffee industry. Finally, drip technology was implemented to carry out irrigation and Perone Hive technology to improve the beekeeping industry.